THE INFLUENCE OF BRAND IMAGE AND DISCOUNT GIVING ON SHOPEE FOOD CUSTOMER LOYALTY WITH CUSTOMER TRUST AS A MEDIATING VARIABLE - Lela Setya Winingtyas; Lina Saptaria (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of brand image and discounts on Shopee Food customer loyalty, with customer trust as a mediating variable. This study uses a quantitative approach with a survey method. The population in this study were all active customers using Shopee Food services. The sampling technique used purposive sampling with a sample size of 150 respondents. Data were measured using a Likert scale of 1-5 ranging from strongly disagree to strongly agree. Data analysis used Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that brand image has a positive and significant effect on customer trust and customer loyalty. Discounts have been shown to have a significant effect on customer trust and customer loyalty, although their direct effect on loyalty is smaller than other variables. Customer trust has the most dominant influence on customer loyalty. Customer trust has been shown to mediate the relationship between brand image and discounts with customer loyalty. These findings provide theoretical contributions to the development of consumer behavior science in the digital era and provide practical input for Shopee Food in designing effective marketing strategies by strengthening brand image, providing relevant discounts, and increasing customer trust.